Elemental speciation of the sediments from cold methane seeps on the Laptev Sea shelf - Irina A. Oberemok; Natalya V. Guseva; Yulia A. Moiseeva; Darya V. Purgina; Natalina A. Poltavskaya; Elena V. Gershelis; Igor P. Semiletov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Relevance. The lack of elemental speciation data in the bottom sediments of the Laptev Sea, as well as the absence of its quantitative changes in occurrence forms in response to methane emissions. Aim. To assess changes in the elemental speciation in areas where methane-containing fluids are discharged. Objects. Nine samples of bottom sediments taken from three horizons of one “cold seep” and two background stations of the outer shelf-continental slope of the Laptev Sea during the AMK-82 expedition aboard R/V “Academician M.V. Keldysh” in autumn 2020. Methods. Sequential extraction BCR (the European Community Bureau of Reference) was performed to determine the elemental speciation in surface sediments; the residual fraction was determined by dissolving in nitric acid. The obtained fraction solutions were analyzed by ICP-MS (NexIon 300D, Perkin Elmer, Waltham, MA, USA), Pyrolysis (Rock-Eval 6 Turbo, Vinci Technologies). Results. The trend towards an increase in element mobility has been identified as a result of a shift in geochemical conditions that is presumably caused by the authigenic carbonate and sulfide formation. Moreover, the increase in the recoverable fraction (associated only with Fe oxides/hydroxides) is highlighted. We assume that the process of unloading methane-containing fluids plays a significant role in enrichment of authigenic carbonates U, Ni, Zn Co, oxides Fe – Sn and V, authigenic sulfides – Co, Mn and W. We also assume the potential formation of chalcopyrite as an authigenic sulfide in methane discharge areas.